Topic shift in Teochew dialect - Saengow, Siriwan (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2023)
This paper presents a research study on topic shift in Teochew dialect. It aims to answer two research questions: 1) What are the types of topic-shifting methods in Teochew? 2) What is the topic-shifting mechanism in Teochew? By using the data collected from the study of Teochew short series on the Chaoshan Wenhua channel through the YouTube video sharing media, there were 10 subjects in total. It was found that there were 2 types of topic shift in Teochew dialect: 1) topic shift in the previous shift; 2) topic shift in the new shift. The topic-shifting mechanism in Teochew can be divided into 3 types: 1) word-level mechanism 2) sentence-level mechanism 3) non-verbal mechanism. The study suggests that subject change in Teochew has a comprehensive mechanism at the word, sentence and non-verbal levels.